Bilateral Giant Fibroadenoma of The Breast: A Case Report - Christian, Jasmine Stephanie; Adiputra, Putu Anda Tusta; Christian, INW Steven (JBN (Jurnal Bedah Nasional); Vol 2 No 2 (2018): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2018.v02.i02.p04, 2018)
Background: fibroadenoma of the breast is one of the ANDI (Aberration of the Normal Development and Involution of the Breast) groups. Benign breast disorders are common in females younger than 30 years, but such masses are not common in juvenile or pre-menarche age groups. The exact pathological diagnosis can be investigated after surgery. For treatment, surgical procedures are needed to remove the lump. Case: a 30-year-old girl visited the outpatient clinic with psychological distress due to the presence of lumps in her both breasts. The lumps have been growing bigger and bigger in the last 3 years. On the physical examination both breasts are huge. FNAB showed the interpretation of atypical ductal hyperplasia and excisional biopsy examination confirmed the presence of bilateral giant fibroadenoma of breast. In this patient, the treatment was carried out in two-staged surgery due to her initial rejection to undergo total breast lumps and tissue removal. Several lumps still remained in the right breast which was indicated for the second surgery. The following surgery was done to remove all of the lumps and breast tissue with reduction breast surgery. Conclusion: conducting breast surgery on the young girl or un-married is not easy as many physical and psychology problems should be considered. Therefore, conducting breast surgery, in this case, should be performed wisely as the recurrence of the lumps was still possible.